Controlled Dietary Restriction With a Prepackaged Low-Residue Diet Before Colonoscopy Offers Better-Quality Bowel Cleansing and Allows the Use of a Smaller Volume of Purgatives: A Randomized Multicenter Trial. Issue 10 (October 2016) - Chou, Chu-Kuang; Chang, Chi-Yang; Chang, Chun-Chao; Chang, Li-Chun; Hsu, Wen-Feng; Chen, Chi-Yi; Wang, Hsiu-Po; Chiu, Han-Mo
Abstract : BACKGROUND: Bowel preparation is burdensome, and less-demanding preparation procedures are needed. Few studies have investigated the effects of low-residue diet and prepackaged low-residue diet in combination with low-volume polyethylene glycol–electrolyte lavage solution during colonoscopy preparation. OBJECTIVE: We compared self-prepared low-residue diets with prepackaged low-residue diets in combination with low-volume polyethylene glycol. DESIGN: This was a single-blinded, 3-arm, multicenter, randomized controlled trial. SETTING: Colonoscopies were conducted in outpatient settings at 3 centers in Taiwan. PATIENTS: The study included 180 patients (age range, 20–75 years) who were scheduled for colonoscopy. INTERVENTIONS: Three groups were compared: group A included self-prepared, 1-day, low-residue diets with a same-day 2.0-L single-dose of polyethylene glycol; group B included prepackaged low-residue diets plus 2.0 L of polyethylene glycol; and group C included prepackaged low-residue diets plus 1.5 L of polyethylene glycol. MAIN OUTCOME MEASURES: The outcome measures were adherence, bowel-cleansing level, and patient satisfaction. RESULTS: One third of the subjects in group A, but none in the prepackaged low-residue diets groups, violated the dietary restrictions. The proportion of right-segment preparation failure was 15.0%, 1.7%, and 6.7% ( p = 0.025). Accordingly, treatment B was superior to A ( p = 0.008). Among subjects violating the low-residue diets guideline, the right-segment preparation failure rate was 25%. According to a multivariate analysis, low-residue diet compliance (adjusted OR = 6.55 (95% CI, 1.83–23.43)) and BMI were predictors of right-sided preparation adequacy, but the volume of polyethylene glycol ingested was not a predictor. Compared with group A, a greater proportion of subjects in groups B and C reported satisfaction. LIMITATIONS: Patients with high BMI and severe constipation were excluded from this study. This study included only an Asian population. CONCLUSIONS: The prepackaged low-residue diet provides excellent adherence, better bowel cleansing, and a better experience than a self-prepared low-residue diet. With good dietary compliance, 1.5 L of polyethylene glycol provides effective preparation. Abstract : Supplemental Digital Content is available in the text.